PERAN PEMERINTAH DALAM PEMBANGUNAN KLUSTER INDUSTRI MILITER : Studi Kasus Lembah Silikon di Bangalore India dan Sekitarnya - Ismiyatun . . (SPEKTRUM, 2013)
Abstract The research was held to investigate India goverment policy in military industry development toward Bangalore silicon valley area as information technology military industry cluster for anticipate revolution on military affairs. India silicon valley development had different type, partnership system with local firm and MNC had roled as pathway to technology transfer and human capital. The novelty is lied on its description about military industry, technology cluster and developmentalist state theory. The cluster is used as development vehicle that could answer sectoral issues especially on military, and information technology because of its technology venture gave power to attain economic diplomacy. The recent researches explored that issue but in fragmented ways, while as general silicon valley was identical with capitalist and neoliberal, but with economic diplomacy, developmentalist state could utilize behind policy to its military industry Keywords : military industry, technology cluster, developmentalist state theory